STUDI LITERATUR: PENGARUH PENGETAHUAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA MAHASISWA - Rofi’ah Rofi’ah; Siti Mardiati; Umi Luthfiyah (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
This study aims to analyze entrepreneurial knowledge on entrepreneurial interest among students. By using the literature study research method. This study refers to 30 journal articles that discuss the topic of the influence of entrepreneurial knowledge on student entrepreneurial interest. The analysis shows that knowledge has a positive and significant influence on entrepreneurial interest in students with a percentage of 93.33%. Entrepreneurial knowledge, including business understanding, management, and innovation, is an important foundation in building students' courage and ability to be entrepreneurs. This research confirms the importance of increasing entrepreneurship learning in higher education to encourage young people to create innovative and independent job opportunities.